In silico analysis of a major allergen from Rattus norvegicus, Rat n 1, and cross-reactivity with domestic pets (2019)
ABSTRACT: Background: Lipocalins play a role in the cellular trafficking of pheromones and are involved in allergic responses to domestic pets. However, the cross-reactivity among allergens of this group has been poorly explored, and the pheromone linking capacity is not well characterized. The aim of this study was to explore cross-reactive epitopes and pheromone linking capacity among Rat n 1 and homologues in domestic pets through an in silico approach. Methods: ElliPro and BepiPred in silico tools were used to predict B cell linear and cross-reactive epitopes. The pheromone linking capacity was explored by docking virtual screening with 2-ethylhexanol, 2,5-dimethylpyrazine, 2-sec-butyl-4,5-dihydrothiazole, and 2-heptanone ligands. Results: According to the analysis, Rat n 1 shares 52% identity with Equ c 1, Can f 6, Fel d 4, and Mus m 1 allergens. The overlapping structures analysis revealed high structural homology (root mean square deviation < 1). Four lineal and three discontinuous epitopes were predicted on Ra t n 1. A lineal epitope located between amino acids residues 24 and 36 was highly conserved on all allergens explored. A cross-reactive discontinuous epitope (T142, K143, D144, L145, S146, S147, D148, K152, L170, T171, T173, D174) was also found. Docking molecular simulations revealed the region involved in linking ligands, and we identified the properties of the binding of four pheromones and the binding potential of Rat n 1. Critical residues for interactions are reported in this study. Conclusions: We identified some possible allergens from Rattus norvegicus, and those allergens could have cross-reactivity with allergens from some animals. The results need to be confirmed with in vitro studies and could be utilized to contribute to immunotherapy and reduce allergic diseases related to lipocalins.